The prevalence, spatial distribution and geographic weighted regression of open defecation practice in sub-Saharan Africa using demographic and health survey (DHS) data - Lidetu Demoze; Natnael Gizachew; Eshetu Abera Worede; Adem Tsegaw Zegeye; Yayeh Walle Molalign; Mitkie Tigabie; Abiy Ayele Angelo; Eyob Akalewold Alemu; Gelila Yitageasu (PLoS ONE, 2025)
Background Open defecation is a harmful and unsafe practice that contributes to environmental pollution and disproportionately affects developing nations, particularly those in Sub-Saharan Africa. According to the World Health Organization (WHO) and the United Nations International Children’s Emergency Fund (UNICEF) Joint Monitoring Programme (JMP), Sub-Saharan Africa is home to 46% of the global population still practising open defecation. Socio-economic factors, cultural norms, and individual attitudes play crucial roles in shaping sanitation behaviours and influencing open defecation practices. Therefore, this study aims to determine the prevalence, spatial distribution, and geographic inequalities of open defecation in Sub-Saharan Africa. Methods A community-based cross-sectional survey was conducted, including 20,130 clusters and 496,957 households from 34 Sub-Saharan African countries. The Demographic and Health Survey (DHS) data were weighted, cleaned, and analyzed using Microsoft Excel, Stata version 17, ArcGIS version 10.7, and SaTScan™ version 10.1. Spatial analyses were performed using ArcGIS version 10.7 and Kulldorff’s SaTScan™ version 10.1, while Geographically Weighted Regression (GWR) analyses were conducted using ArcGIS version 10.7. Results The prevalence of open defecation among households in Sub-Saharan Africa was 23.24% (95% CI: 23.12–23.35). The practice was clustered across enumeration areas (Global Moran’s I = 0.25, Z-score = 366.12, P-value ≤ 0.001). The Getis-Ord Gi* statistic identified hotspots of open defecation primarily in East Africa, Central Africa, and West Africa. Anselin Local Moran’s I detected both high and low clusters of open defecation, while SaTScan cluster analysis identified 146 windows containing significant clusters of households practising open defecation across Sub-Saharan Africa. Geographically Weighted Regression (GWR) analysis revealed that several factors were positively associated with open defecation, including lack of educational attainment, unimproved drinking water sources, lack of basic access to water, younger household heads, and extreme poverty. Additionally, household size greater than four, the richest households and urban and rural residency were negatively associated with open defecation practices. Conclusion This study reveals a high prevalence of open defecation (23.24%) in Sub-Saharan Africa with significant geographic clustering, particularly in East, Central, and West Africa. This estimate is higher than the 18% reported by the 2021 WHO/UNICEF Joint Monitoring Programme (JMP). Novel spatial and GWR analyses uncovered associations with poverty, lack of education, water access, age of household heads, and wealth status. These findings underscore the need for geographically targeted, multi-sectoral sanitation interventions that address underlying socio-demographic disparities. Future research should explore the effectiveness of spatially tailored programs and integrate behavioral insights to accelerate progress toward Sustainable Development Goal 6.